Light microscopy of the endoplasmic reticulum-membrane contact sites in plants - Zang, J; Zhang, T; Hussey, P J; Wang, P (Journal of microscopy, 2020)
The existence of membrane contact sites (MCS) has been reported in different systems in the past decade, and their importance has been recognised by the cell biology community. Amongst all endomembrane structures, the endoplasmic reticulum (ER) plays vital roles in organising the organelle interaction network with the plasma membrane (PM), Golgi bodies, mitochondria, plastids, endosomes and autophagosomes. A number of methods have been used to study the establishment and functions of these interactions, among them, light microscopy appears to be one of the most effective approaches. Here, we present an overview of the discovery of ER-PM contact sites, and highlight the latest developments in light microscopical-based techniques that can be used for their study.
Keywords: buněčná membrána; Plant Proteins; light microscopy; ER-PM contact sites; Endoplasmic reticulum; endoplazmatické retikulum; membrane contact sites; fluorescenční barviva; Cell Membrane; Microscopy; Fluorescent Dyes; plants; Endoplasmic Reticulum; rostlinné proteiny; mikroskopie; Plant Cells; rostlinné buňky